2015
DOI: 10.3906/vet-1410-65
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented cottonseed meal on the growth performance, apparent digestibility, carcass traits, and meat composition in yellow-feathered broilers

Abstract: The effects of supplementing broilers' diets with fermented cottonseed meal (FCSM) on the broilers' performance, apparent digestibility, carcass traits, and meat composition were studied. A total of 180 yellow-feathered chickens of 21 days old were randomly divided into three groups (six replicates of 10 broilers each): 1) a control group (Con), 2) a treatment group of FCSM by Candida tropicalis (Ct), and 3) a treatment group of FCSM by C. tropicalis plus Saccharomyces cerevisiae (Ct-Sc). Results showed that F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
(33 reference statements)
4
27
1
Order By: Relevance
“…More specifically, Henry et al (2001) reported that CSM significantly increased abdominal fat content (as a percentage of body weight) in 7-to 21-d-old broilers. However, in a previous study, we showed that FCSM supplementation significantly reduced the abdominal fat content of 21-to 42-d-old broilers (Nie et al, 2015), whereas in the current study, no significant differences were detected when the birds were reared up to 64 days. Therefore, this …”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…More specifically, Henry et al (2001) reported that CSM significantly increased abdominal fat content (as a percentage of body weight) in 7-to 21-d-old broilers. However, in a previous study, we showed that FCSM supplementation significantly reduced the abdominal fat content of 21-to 42-d-old broilers (Nie et al, 2015), whereas in the current study, no significant differences were detected when the birds were reared up to 64 days. Therefore, this …”
Section: Discussionmentioning
confidence: 38%
“…This consistent with the notion that fatty acid β-oxidation increases by upregulating the transcription level of PPAR-α. The obvious upregulation of hepatic PPAR-α and LPL was associated with better gain-tofeed ratio and nutrient digestibility when FCSM was added to the diet (Nie et al, 2015), and the difference between the male and female broilers results in different growth rates.…”
Section: Effect Of Cottonseed Meal Fermented With Yeast On the Lipid-mentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant results were reported by Hossain et al (2012) and Nie et al (2015), in which dietary supplementation with fermented Alisma canaliculatum and Candida tropicalis-fermented cotton seed, respectively, increased the crude protein content of breast meat of broiler chicks. The mechanism by which AC-FCP increased the protein content of breast meat is unclear, but the enhancing effect of probiotic fungus grown in AC-FCP on the protein efficiency ratio and thus production of protein in the musculature of broilers may be the reason (Khaksefidi & Rahimi, 2005;Hossain et al, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Sun et al (2015a) reported that fermentation of CSM with B. subtilis BJ-1 significantly reduced FG level and increased CP level. Nie et al (2015) reported that CSM fermented by Candida tropicalis and C. tropicalis plus Saccharomyces cerevisiae significantly improved CP and crude fat levels. Gadelha, Fonseca, Oloris, Melo, and Sotoblanco (2014) reported that FG can significantly inhibit growth performance and increase mortality in broilers.…”
Section: Discussionmentioning
confidence: 99%